PREPARATION AND EVALUATION OF PULSATILE DRUG DELIVERY OF FLUVASTATIN SODIUM - Kumar P, Jitendra; Y, INDIRA MUZIB; Misra, Gitanjali (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT In the present study, an attempt was made to develop the pulsatile drug delivery of fluvastatin sodium to the colon. Formaldehyde-treated capsule bodies were used for the preparation of pulsincaps. It was sealed with a unhardened cap of the capsule. The microspheres were prepared by emulsion solvent evaporation technique. Optimized microsphere formulations were selected based on dissolution studies. Hydrogel plug (HP) (Karaya gum and lactose in 1:1 ratio) having 4.5 kg/cm hardness and 100 mg weight was placed in the capsule opening and found that it was satisfactory to retard the drug release in small intestinal fluid and to eject out the plugin colonic fluid and releasing the microspheres into colonic fluid after a lag time criterion of 5 hrs. The sealed capsules were completely coated by dip coating method with 5% cellulose acetate phthalate to prevent variable gastric emptying. Dissolution studies of pulsatile capsule device in media with different pH (1.2, 7.4 and 6.8) showed that drug release in the colon could be modulated by optimizing the concentration of polymers in the microspheres. Drug-polymer interaction studies indicated no interaction in between the drug and the polymer. Among all the formulations, fluvastatin sodium microspheres prepared with Eudragit RS 100 in 1:3 ratio shown prolonged release for a period of 12 hrs. The obtained results showed the capability of the system in delaying drug release for a programmable period of time and to deliver the drug in the early morning hours when cholesterol synthesis are more prevalent. 2 Keywords: Fluvastatin sodium, Pulsatile, Hydrogel plug.